Gambaran Pengelolaan Emergency Kit (Trolley) Di Rumah Sakit Umum Daerah (RSUD) dr. Hasri Ainun Habibie Kabupaten Gorontalo - Abdulkadir, Widysusanti; Tuloli, Teti S.; Pakaya, Adela (Indonesian Journal of Pharmaceutical Education, 2021)
An emergency kit is life-saving drug storage that is immediately required for helping patients with a sudden decline in health status. Therefore, the management of an emergency kit should be taken into concern. This qualitative descriptive research is devoted to determining the management of the emergency kit (trolley) from the aspects of recording and reporting, arrangement, human resources, facilities, and infrastructure in Regional Public Hospital RSUD Hasri Ainun Habibie in 2019. The obtained data were analyzed based on the Regulation of the Minister of Health Number 72 of 2016 Concerning Standards of Pharmaceutical Services in Hospitals and the Standard Operating Procedures of the hospital mentioned earlier. Further, this study involved pharmacy staff as the responsible person of the Trolley and Emergency Trolley themselves as the sample. The results indicate that the wards, in terms of the recording and reporting processes, have not reached good management. It is revealed that out of seven wards that provide emergency trolley, 100% of them have not fulfilled the sub-variable on recording the taking of emergency stocks in the aspect of recording and reporting; 100% have not satisfied the sub-variable on using the key of disposable trolley in the aspect of arrangement; in the aspect of human resources, 100% and 50% have not met the sub-variables on the signing of the handover letter and trolley locking, respectively, and 25% have done the gradual stocks checking; in the aspect of facilities and infrastructure, 100% have not fulfilled the sub-variable on disposable lock document.